Kepatuhan Pengobatan Multi-Drug Therapy (MDT) dan Faktor yang Mempengaruhinya pada Pasien Morbus Hansen di RSUD RAA Soewondo Pati - Elly Mazida; Erna Kristiyani; Shirly Gunawan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Hansen’s disease (leprosy) remains a public health problem in Indonesia. Although national elimination was declared in the year 2000, the number of new cases has remained stagnant at around 17,000–20,000 cases per year, and the proportion of Grade 2 Disability (G2D) remains high. Social stigma, delayed diagnosis, and poor adherence to Multi-Drug Therapy (MDT) continue to be major challenges in achieving elimination. This study aims to evaluate MDT adherence based on three Hansen’s disease patients and to analyze the factors influencing it. This research uses a descriptive design with a three-case report approach analyzed from a public health perspective. The variables assessed include MDT adherence, family support, stigma, patient knowledge, and drug adverse effects. Two of the three patients demonstrated high adherence to MDT, while one patient exhibited non-adherence due to a severe drug reaction (dapsone hypersensitivity syndrome). Factors influencing adherence include patient knowledge, drug side effects, family support, and special conditions such as pregnancy. MDT adherence remains a challenge in leprosy elimination efforts. A multidisciplinary approach involving education, intensive monitoring, and stigma prevention is needed to improve treatment success.